Seed dimorphism, nutrients and salinity differentially affect seed traits of the desert halophyte Suaeda aralocaspica via multiple maternal effects - Wang, Lei (BioMed Central, 2012)
BACKGROUND: Maternal effects may influence a range of seed traits simultaneously and are likely to be context-dependent. Disentangling the interactions of plant phenotype and growth environment on various seed traits is important for understanding regeneration and establishment of species in natural environments. Here, we used the seed-dimorphic plant Suaeda aralocaspica to test the hypothesis that seed traits are regulated by multiple maternal effects. RESULTS: Plants grown from brown seeds had a higher brown:black seed ratio than plants from black seeds, and germination percentage of brown seeds was higher than that of black seeds under all conditions tested. However, the coefficient of variation (CV) for size of black seeds was higher than that of brown seeds. Seeds had the smallest CV at low nutrient and high salinity for plants from brown seeds and at low nutrient and low salinity for plants from black seeds. Low levels of nutrients increased size and germinability of black seeds but did not change the seed morph ratio or size and germinability of brown seeds. High levels of salinity decreased seed size but did not change the seed morph ratio. Seeds from high-salinity maternal plants had a higher germination percentage regardless of level of germination salinity. CONCLUSIONS: Our study supports the multiple maternal effects hypothesis. Seed dimorphism, nutrient and salinity interacted in determining a range of seed traits of S. aralocaspica via bet-hedging and anticipatory maternal effects. This study highlights the importance of examining different maternal factors and various offspring traits in studies that estimate maternal effects on regeneration.